The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18041941
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Pharmacovigilance Systems within the Neglected Tropical Diseases Programs in East Africa—Ethiopia, Kenya, Rwanda, and Tanzania

Abstract: Monitoring the safety of medicines used in public health programs (PHPs), including the neglected tropical diseases (NTD) program, is a WHO recommendation, and requires a well-established and robust pharmacovigilance system. The objective of this study was to assess the pharmacovigilance systems within the NTD programs in Ethiopia, Kenya, Rwanda, and Tanzania. The East African Community Harmonized Pharmacovigilance Indicators tool for PHPs was used to interview the staff of the national NTD programs. Data on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In most SSA countries, schistosomiasis and STH are coendemic, hence praziquantel and albendazole are coadministered during MDA. Although coadministration of the two drugs targeting the two NTDs is cost effective, several factors, including risk for drug interaction and overlapping toxicities, underscores the need for safety monitoring [ 14 , 15 ]. Safety monitoring is essential to detect the number, type, and severity of AEs and identify risk factors associated with mass albendazole and praziquantel administration-related AEs for timely interventions, thereby minimizing harm and sustaining public confidence in the MDA [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most SSA countries, schistosomiasis and STH are coendemic, hence praziquantel and albendazole are coadministered during MDA. Although coadministration of the two drugs targeting the two NTDs is cost effective, several factors, including risk for drug interaction and overlapping toxicities, underscores the need for safety monitoring [ 14 , 15 ]. Safety monitoring is essential to detect the number, type, and severity of AEs and identify risk factors associated with mass albendazole and praziquantel administration-related AEs for timely interventions, thereby minimizing harm and sustaining public confidence in the MDA [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, millions of children receive periodic MDA of praziquantel and albendazole in SSA, including Rwanda, but safety data from large-scale active cohort event monitoring (CEM) studies are scarce partly due to lack of fully functional pharmacovigilance systems [ 14 , 21 , 22 ]. The NTD programs prioritize MDA coverage and AEs are often managed and contained at the sites they happened for fear of rumors, which may negatively affect public confidence, and are not reported to the National Medicines Regulatory Authorities (NMRAs) [ 14 , 22 ]. The underreporting of AEs during MDA campaigns makes it challenging to accurately estimate the risks of medicine-related harm and inform healthcare policy and practice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…National medicines regulatory authorities in Africa, including the Tanzania Medicines and Medical Devices Authority (TMDA) strive to obtain safety data after marketing authorization of many drugs [ 10 , 11 ]. A recent comparative assessment of the pharmacovigilance systems in the NTD Programs in four East African countries indicated that no adverse events following MDA were reported to the National Medicines Regulatory Authorities despite millions of people being exposed to MDA in the year 2017/2018 [ 12 ]. Various initiatives have been undertaken to reverse the status-quo, and different methods have been introduced to increase the number of reports.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale safety surveillance studies are pivotal in detecting rare severe adverse events [ 16 ]. Although millions of people in Africa are receiving periodic MDA, safety data from large-scale active CEM studies are scarce partly due to the lack of fully functional pharmacovigilance systems in the region [ 10 , 11 , 12 ]. The WHO’s global individual case safety reports database (VigiBase) recently reported serious suspected ADRs and safety signals associated with ivermectin use and the under-reporting of ADRs in SSA [ 17 ].…”
Section: Introductionmentioning
confidence: 99%